Type III secretion translocon assemblies that attenuate Yersinia virulence. (21st January 2013) - Costa, Tiago R. D.; Amer, Ayad A. A.; Farag, Salah I.; Wolf‐Watz, Hans; Fällman, Maria; Fahlgren, Anna; Edgren, Tomas; Francis, Matthew S.
Summary Type III secretion enables bacteria to intoxicate eukaryotic cells with anti‐host effectors. A class of secreted cargo are the two hydrophobic translocators that form a translocon pore in the host cell plasma membrane through which the translocated effectors may gain cellular entry. In pathogenic Yersinia, YopB and YopD shape this translocon pore. Here, four in cis yopD mutations were constructed to disrupt a predicted α‐helix motif at the C‐terminus. Mutants YopDI262P and YopDK267P poorly localized Yop effectors into target eukaryotic cells and failed to resist uptake and killing by immune cells. These defects were due to deficiencies in host‐membrane insertion of the YopD–YopB translocon. Mutants YopDA263P and YopDA270P had no measurable in vitro translocation defect, even though they formed smaller translocon pores in erythrocyte membranes. Despite this, all four mutants were attenuated in a mouse infection model. Hence, YopD variants have been generated that can spawn translocons capable of targeting effectors in vitro, yet were bereft of any lethal effect in vivo. Therefore, Yop translocators may possess other in vivo functions that extend beyond being a portal for effector delivery into host cells.